Development of Algorithm for Preservation of Heritage Murals and Painting Using Image Processing - S. Lalithakumari; Pandian R (Institute of Advanced Engineering and Science, 2018)
Image archiving and preservation finds extensive application in culture heritage murals. The study of cultural heritage is of the extreme importance at national and international levels. Not only global organizations like UNESCO but also museums, libraries, culture, temples and private initiatives are working in these directions. During the last three decades, researchers in the field of imaging discipline have started to contribute an increasing set of algorithms for cultural heritage; in that way providing indispensable support to these efforts. A better comparison of the different compression methods presented in this proposed work for culture Heritage mural images. Compression methods usually applied some method to reduce the number of components within each spectrum. The effectiveness of mural image archiving and preservation is analyzed based on 2-D wavelets filtering. The optimum algorithm is also found based on the results.